Outcomes of salvage radical prostatectomy after initial irreversible electroporation treatment for recurrent prostate cancer. (13th May 2022) - van Riel, Luigi A.M.J.G.; Geboers, Bart; Kabaktepe, Ertunc; Blazevski, Alexander; Reesink, Daan J.; Stijns, Pascal; Stricker, Phillip D.; Casanova, Juan; Dominguez‐Escrig, Jose Luis; de Reijke, Theo M.; Scheltema, Matthijs J.; Oddens, Jorg R.
Abstract : Objective: To evaluate: (i) safety, (ii) feasibility, and medium‐term (iii) oncological and (iv) functional outcomes of salvage radical prostatectomy (sRP) for recurrent localised prostate cancer (PCa) following initial focal therapy using irreversible electroporation (IRE). Patients and Methods: An international, multicentre and retrospective analysis of prospectively collected data of patients that underwent sRP for recurrent localised PCa after initial primary IRE treatment. Data were reported on (i) surgical complications, (ii) feasibility of sRP reported by surgeons, (iii) time interval between IRE and sRP and pathology results, and (iv) urinary continence, erectile function, and quality of life. Results: In four participating centres, a total of 39 patients with a median (interquartile range [IQR]) age 64 (60–67) years were identified. No serious adverse events occurred during or following sRP and surgery was deemed feasible without difficulties. The median (IQR) time to recurrence following IRE was 14.3 (9.1–38.8) months. Pathology results showed localised disease in 21 patients (53.8%) and locally‐advanced disease in 18 (46.2%). Positive surgical margins (PSMs) were observed in 10 patients (25.6%), of which six (15.4%) had significant PSMs. A persistent detectable prostate‐specific antigen level was found in one case after sRP, caused by metastatic disease. One patient had a biochemical recurrence 6 months after sRP. These two cases, together with a PSM case, required additional therapy after sRP. After a median (IQR) follow‐up of 17.7 (11.8–26.4) months, urinary continence and erectile function were preserved in 34 (94.4%) and 18 patients (52.9%), respectively, while quality of life remained stable. Conclusions: Salvage RP is safe and feasible for patients with recurrent localised PCa following initial IRE treatment. The medium‐term oncological and functional outcomes are similar to primary RP. Strict patient selection for focal therapy and standardised follow‐up is needed as some patients developed high‐grade disease.